Convergência regulatória na Integraç\~ao comercial Brasil-Argentina: Os impactos da regulaç\~ao e da normalizaç\~ao técnica sobre o comércio internacional - Vera Thorstensen; Luís Fernando Tironi; Mauro Kiithi Arima Júnior; Tiago Matsuoka Megale (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– The present article aims to compare the regulatory and technical standardization systems in Brazil and Argentina, in order to examine the degree of convergence existing and possible between the two trade partners. Understanding the regulatory and standardization characteristics of the two countries is essential to analyze some of the acute problems of the integration process in Mercosur. The examination of regulations, technical standards and the regional instruments to regulatory convergence in these countries makes it possible to compare the level of compatibility between the two regulatory frameworks, as well as to formulate proposals for deepening the regional integration process within Mercosur.
Keywords: F10; F13; Q17; 330; Brazil; Argentina; regulation; technical standards; TBT; Mercosur